Implementasi Website Analisis Beban Kerja Pegawai pada Kecamatan Krembangan, Kota Surabaya - Farhana, Yustanti Aprinda; Hardjati, Susi (VISA: Journal of Vision and Ideas, 2024)
The central government has passed Law Number 5 of 2014 concerning Civil Apparatus with the aim of realizing good governance and creating a state apparatus with high professionalism. The government is obliged to organize accountable management of apparatus resources through the management of Civil Servants. This arrangement is carried out through workload analysis, which is a stage for determining the number of working hours needed to complete a job within a certain time and determining the number of personnel, as well as the appropriate amount of responsibility or workload. Therefore, the Organization Section of the Surabaya City Regional Secretariat created a workload analysis website or e-ABK which has been implemented in each agency within the Surabaya City Government. This research uses descriptive qualitative research. Data collection techniques were carried out using observation, interviews and literature study methods. The results of the implementation of filling in e-ABK for employees in Krembangan District, Surabaya City have not run optimally because there are still problems with employees filling in supporting data on the ABK website which is not valid. Apart from that, they also still don't understand the analysis of workload implementation because the Organizational Section of the Surabaya City Regional Secretariat did not carry out outreach until they understood. However, they should take the initiative to carry out sharing activities between sub-district employees so that they understand more about the implementation of workload analysis.